Identifying crop productivity constraints and opportunities using focus group discussions: A case study with farmers from Tigray. (1st September 2016) - Kraaijvanger, R.; Almekinders, C.J.M.; Veldkamp, A.
Highlights: Focus group discussions reflected contextual diversity. Farmer groups considered soil fertility measures an important opportunity. Quantification of focus group outcomes supported its wider application. Abstract: Crop productivity in many places in Sub Saharan Africa is low. This affects food security and rural livelihoods. Identification of constraints and opportunities is a first and essential step in development processes aiming at improving crop productivity. Macro- and meso-level diagnostic methods frequently point to soil fertility and agronomic practices as major constraints. In Tigray, our study area in Northern Ethiopia, we applied focus group discussion in four locations to identify productivity constraints and opportunities. Outcomes in the form of "mind maps" were quantified to allow comparison between the locations. We found that, apart from some similarities, outcomes demonstrated much diversity. Location specific conditions and agronomic factors were considered main constraints by farmer groups in all locations. Soil fertility measures were considered a main opportunity. However, other categories of constraints and opportunities, like economic factors and irrigation, were diverse for the locations involved. Observed outcome variability was supported by descriptive biophysical and socio-economic data. We concluded that superficial identification of constraints and opportunities neglected contextual diversity. Making such diversity visible is essential in understanding and addressing this complexity. Applying approaches like focus group discussion, therefore, offers important opportunities at grassroots-level to give farmers a mandate and responsibility at early stages of development processes.